Effect of vitamin A on bone resorption: evidence for direct stimulation of isolated chicken osteoclasts by retinol and retinoic acid. - Oreffo, R; Teti, A; Triffitt, J; Francis, M; Carano, A; Zallone, A (1988)
The effects of retinol (vitamin A) and retinoic acid on primary cultures of isolated chicken osteoclasts have been studied. The experiments were performed to establish the direct actions of these two agents on the organization of cytoskeletal structures, on the acid phosphatase contents, and on the bone resorption activities of these cells. The results showed that by treating the cultures with retinol or retinoic acid, from 10(-8) to 10(-5) M, there were dose-related responses of the osteoclasts. Adhesion to the substratum was stimulated by increasing the number of cells exhibiting the specialized dot-like adhesion structures, or podosomes, which represent the active part of the sealing zone. The treatments also induced rearrangement of the microtubular patterns with reversible depolymerization of microtubules. Acid phosphatase activity was significantly higher both in vitamin A-treated osteoclasts and in their media. When [3H]proline-labeled bone particles were added to the retinoid-treated osteoclasts, the release of [3H]proline was increased significantly compared to controls. These results suggest that the two vitamin A metabolites cause several modifications of the metabolic status of isolated osteoclasts that result in augmented rates of bone resorption.